Effect Combine DrillOn Increasing Passing In 14 Year OldPlayers Ssb Gerdu Papak Plandi - Pungky, Roy; Kurniawan, Wing Prasetya; Himawanto, Wasis (CV. Nusantara Sporta, 2024)
This research is based on the researcher's observations and experience that the 14-year-old SSB Gerdu Papak Plandi Jombang soccer player has not mastered the down-passing technique well. SSB coach Gerdu Papak Plandi Jombang, assisted by researchers, found a solution to correct passing technique errors. The average player's lower passes are less accurate and do not pay attention to technique. This research used a quantitative approach with the subject being a 14-year-old SSB Gerdu Papak Plandi player, using an under-the-ball passing test. The results of the research show that the combination of passing drill training has a significant influence on players' passing skills, with a calculated t value of 2.086 > t table 1.724 and a significant value of 0.009 < 0.05, as well as a percentage increase of 17.87%. In conclusion, there is a significant effect of combination passing training on the passing skills of 14-year-old soccer players at SSB Gerdu Papak Plandi Jombang.